Financial stability and monetary policy of the Central Bank of West African Countries: a Markov-Switching model - HOUNGBEDJI, Honoré S; BASSONGUI, Nassibou (My University, 2023)
Purpose – This paper aims to examine the response of monetary policy to financial instability in the West African Economic and Monetary Union. Design/methodology/approach – Through annual aggregated data from 1970 to 2019, the empirical strategy is based on the Markov regime-switching model with fixed probabilities. Findings – The results revealed that the monetary policy of the central bank of the West African Economic and Monetary Union is characterized by two regimes (calm and distress) with respect to the trend of financial stability. The authors also found that the occurrence of the calm regime was likely greater than that of the distress regime. In addition, the calm regime is longer than the distress regime. The authors finally revealed that the central bank reacts to financial instability risk by increasing its short-term interest rate when financial instability reaches a threshold. Research limitations/implications – The limitation of this study is the unavailability of monthly or quarterly data that are more suitable for the methodological approach adopted. Originality/value – This study is the one to estimate the response of the Central Bank of West African Countries to financial stress using a novel approach based on the Markov-Switching regression.
Keywords: Financial stability; Monetary policy; Markov regime switching model